FREE RADICAL SCAVENGING ACTIVITY OF ALLIUM ASCALONICUM - T. VANITHA,; K. J. UMADEVI,; K. VIJAYALAKSHMI, (The Bioscan, 2011)
50g of Allium ascalonicum L was homogenized in 100 mL of methanol and the extract was used for the determination of radical scavenging activity, chain-breaking activity and reducing capacity. Time dependent free radical scavenging activity was studied for 20, 40 and 60 mg of extract of A.ascalonicum. It was observed that 20mg extract A. ascalonicum scavenges 43 % after 5 hr and 60% after 24 hr. Ascorbic acid (control) had showed 84% of NO scavenging activity while 60 mg of A.ascalonicum extract showed nearly 60% of NO scavenging activity which is highly significant. The free radical scavenging effect of A.ascalonicum could be due to high amounts of quercetin present in it. The other phytochemicals present in the extract of A.ascalonicum could have the synergetic effect. These findings are correlated with its phytochemical analysis.